Experimental verification of slag-cement mortar compressive strength predicted using neural network analysis [electronic resource] - 386371 Marylynn, Chung Li Li; Fakulti Kejuruteraan Awam (2008)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur dan Bahan)) - Universiti Teknologi Malaysia, 2008